2012
DOI: 10.1534/g3.112.004614
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Mps3 SUN Domain Mutants inSaccharomyces cerevisiaeReveals an Interaction with the SUN-Like Protein Slp1

Abstract: In virtually all eukaryotic cells, protein bridges formed by the conserved inner nuclear membrane SUN (for Sad1-UNC-84) domain-containing proteins and their outer nuclear membrane binding partners span the nuclear envelope (NE) to connect the nucleoplasm and cytoplasm. These linkages are important for chromosome movements within the nucleus during meiotic prophase and are essential for nuclear migration and centrosome attachment to the NE. In Saccharomyces cerevisiae, MPS3 encodes the sole SUN protein. Deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 86 publications
0
39
1
Order By: Relevance
“…Perhaps, the SPB has a role in controlling lipid homeostasis in the NE as part of a normal coordination of events during cell division. Previous work indicates that the SPB protein Mps3 is involved in NE homeostasis in addition to its role in SPB duplication 37 , 42 . Although we found that two Mps3 ts mutations, mps3–1 -and mps3–7 , also affect Trm1-II-GFP location, our work suggests a broader role for the SPB in NE homeostasis.…”
Section: Discussioncontrasting
confidence: 56%
“…Perhaps, the SPB has a role in controlling lipid homeostasis in the NE as part of a normal coordination of events during cell division. Previous work indicates that the SPB protein Mps3 is involved in NE homeostasis in addition to its role in SPB duplication 37 , 42 . Although we found that two Mps3 ts mutations, mps3–1 -and mps3–7 , also affect Trm1-II-GFP location, our work suggests a broader role for the SPB in NE homeostasis.…”
Section: Discussioncontrasting
confidence: 56%
“…These findings expand also the known roles of the mid-SUN-domain proteins. The other known members of this family show similar ER/NE localization and have been implicated in a diversity of processes, including folding of integral membrane proteins in budding yeast (15,16), cell proliferation and differentiation in amoeba (14), regulation of bone formation in mouse (13,17), and dehydration signaling in chickpea (30). Sordaria represents thus the first instance, to our knowledge, in which a member of this family is implicated in karyogamy.…”
Section: Discussionmentioning
confidence: 94%
“…The precise role of those proteins remains unknown. Budding yeast Slp1 is implicated in folding of integral membrane proteins and is involved directly or indirectly in Sun1/Mps3 localization to the NE (15,16). Dictyostellum discoideum SunB protein plays roles in both cell proliferation and differentiation (14).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…This has recently been supported by the characterization of the S. cerevisiae mid-SUN protein SLP1 (SUN-like protein) and its interaction with the classical C-terminal yeast SUN protein Msp3. 13 Findings presented by several participants (Bass, Graumann and Tatout) on the previously uncharacterized mid-SUN proteins provide an example in which the plant field leads research efforts to identify and characterize novel nuclear envelope components. Both Graumann and Christophe Tatout (Blaise Pascal University, France) presented information about the molecular interactions of Arabidopsis SUN proteins.…”
mentioning
confidence: 99%